International Experience of Establishing Technology Transfer Centers at the Universities - Lysenko, V.S.; Yehorov, S.O.; Diatchyk, D.I. (Science and Innovation, 2024)
The experience of creation and operation of technology transfer centers based on US universities has been analyzed in order to adopt the best practice for the creation of such centers in Ukraine.